Blackness at the Intersection - Mxalisa, Asiphe; Sonkosi, Abongile (Critical Studies in Teaching and Learning, 2024)
Crenshaw, K., Andrews, K. and Wilson, K. (Eds.) 2024. Blackness at the Intersection. London: Bloomsbury Press.